2015
DOI: 10.1016/j.celrep.2015.06.040
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Reprogramming of Striatal NG2 Glia into Functional Neurons that Integrate into Local Host Circuitry

Abstract: SummaryThe possibility of directly converting non-neuronal cells into neurons in situ in the brain would open therapeutic avenues aimed at repairing the brain after injury or degenerative disease. We have developed an adeno-associated virus (AAV)-based reporter system that allows selective GFP labeling of reprogrammed neurons. In this system, GFP is turned on only in reprogrammed neurons where it is stable and maintained for long time periods, allowing for histological and functional characterization of mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
161
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 27 publications
4
161
0
1
Order By: Relevance
“…Astrocytes and NG2 cells can be reprogrammed to neurons by expressing proneural transcription factors in the cerebral cortical and subcortical regions 1720 . Recordings from cortical slices and rabies-virus-based tracings indicate that these neurons are functional.…”
mentioning
confidence: 99%
“…Astrocytes and NG2 cells can be reprogrammed to neurons by expressing proneural transcription factors in the cerebral cortical and subcortical regions 1720 . Recordings from cortical slices and rabies-virus-based tracings indicate that these neurons are functional.…”
mentioning
confidence: 99%
“…To this end, Parmar and colleagues have developed refined tools to study the conversion of Ng2 glia to GABAergic and glutamatergic neurons and their integration into the host brain (Torper et al, 2015). Using Cre-recombinase-dependent AAV vectors, they delivered Ascl1, Lmx1a, and Nurr1 specifically to NG2 glia in the striatum of adult mice and monitored neuronal conversion and circuit integration through a novel neuron-specific reporter.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery of betacellulin (BTC), a member of EGF family, into the lateral ventricle induced the expansion of NSCs and neuroblasts, as well as neurogenesis in the olfactory and dentate gyrus [104]. Interestingly, recent studies have shown that endogenous repair mechanisms are not limited to neurogenic niches as glial cells including astrocytes, oligodendrocyte precursors, and pericytes can be reactivated following ischemia and differentiate into neurons [105][106][107].…”
Section: Exploiting Endogenous Neurogenesismentioning
confidence: 99%